Perception and adoption of competency-based training by academics in Ghana - Camillus Abawiera Wongnaa; Williams Kwasi Boachie (SpringerOpen, 2018)
Abstract Background With the rise in graduate unemployment and the poor linkage between university education and industry, competency-based training (CBT) is gaining popularity in Ghana's universities as a way of producing business-oriented and well-grounded graduates for industry who are ready to make use of knowledge acquired in university education to establish businesses that will help reduce unemployment in the country as well as working effectively in the nation's industry and service sectors. With CBT yet to be introduced in most Ghanaian tertiary institutions, information about academics' perception and willingness to adopt the methodology is crucial. This study examined the perception and adoption of CBT by academics in Ghana using cross-sectional data collected from 300 faculty members of Kwame Nkrumah University of Science and Technology (KNUST) using a structured questionnaire. Descriptive statistics, 5-point Likert scale, perception index, and the logit model were the methods of analysis employed. Results The results of the survey showed that the overall perception index was 0.49, indicating that generally faculty members of KNUST agreed and had a positive perception of the potential of CBT in instilling in students employable skills. The logit results also showed that the probability of adoption of CBT is positively influenced by participation in CBT workshops, effective supervision of faculty members by university authorities, availability of teaching aids, and availability of incentives. Conversely, adoption was found to be negatively influenced by teaching load and number of undergraduate students per class. Conclusions We conclude that provision of appropriate teaching and learning resources that complement adoption of CBT, incentives, and competency-based education training for academics by university authorities and stakeholders in Ghana's tertiary education will enhance the adoption of CBT methodologies.